Pengaruh Kualitas Pelayanan dan Harga terhadap Kepuasan Pelanggan pada Kopi Nako Lebak Bulus Jakarta - Putri, Aldila Rahma; Savitri, Shela Indah (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
This research was conducted to explore the factors influencing customer satisfaction in the highly competitive food and beverage industry, particularly in the context of Kopi Nako Lebak Bulus. With the growing number of coffee shop businesses, customer satisfaction has become a crucial determinant of business success and sustainability. Companies must understand which aspects most significantly influence their customers' experiences. Therefore, this study aims to examine the effect of service quality and pricing, both partially and simultaneously, on customer satisfaction. A quantitative approach was employed using a survey method, with a total of 99 respondents selected through a simple random sampling technique. Data was collected through a structured questionnaire. The analytical tools used include simple linear regression analysis, correlation and determination coefficient tests, as well as validity, reliability, normality, multicollinearity, autocorrelation, heteroscedasticity, t-tests, and F-tests. The findings reveal that both service quality and price have a positive and significant impact on customer satisfaction, individually and jointly. This indicates that improving service quality and offering reasonable pricing are essential strategies to enhance customer experience. Consequently, management should prioritize these factors to foster customer loyalty and achieve a sustainable competitive advantage in the marketplace.